Impact of Technological Investment and Ownership Structure on the Profitability of Commercial Banks: Evidence from Vietnam - Nguyen Minh Nhat (Ianna Journal of Interdisciplinary Studies)
Background: COVID-19 has influenced various aspects of people's lives and many industries and sectors of the economy, including banking. Commercial banks must improve operational efficiency as economies integrate, and catalyst improves banks' operational performance to increase competitiveness, market share, and sustainable growth.